PRESENTATION OF OZAN IMAGE IN NABI KHAZRI DRAMATURGY (BASED ON THE PLAY "THE SWORD STUCK IN THE GROUND") - Hasanova Narmin Tarlan (Modern Scientific Method, 2024)
People's poet Nabi Khazri (1924-2007) left a deep mark on the 20th century Azerbaijani literature with his poetic world, epic and dramatic creativity. Love of the homeland, attachment to the land, the homeland was the main rock of Nabi Khazri's creativity. His ideal was to introduce our national and moral values to the world and he did it well. "Since the political moderation that began in the early fifties with the disappearance of the Stalin and Bagirov regimes lifted the atmosphere of repression and violence over the literary and cultural life, a new breath of folklore began to be heard in fiction. The lifting of the political ban on the "Kitabi-Dade Gorgud" epic and the vindication of the magnificent folk epic was one of the most important events in this historical stage" [[H.Araslı, Ə.Dəmirçizadə, M.Təhmasib. “Dədə-Qorqud dastanları”]. In the already written works, class and national values came face to face, and the trends of class approach, which began to decrease in the 60s, were completely eliminated in the 80s. Fiction literature played the role of a leading force in solving the problems of national self-awareness, national identity, returning to one's roots, and returning to oneself. It is not by chance that the famous poet Nabi Khazri also painted the world of Dede Gorgud in his work and painted our national and human values with new colors. In the 1980s, he wrote the poem "Legendary Dreams", the plays "Sword stuck in the ground" and "Burla Khatun" based on "During the Looting of Salur Ghazan's House", which resonated with the demands of modernity in dramaturgy. Until Nabi Khazri, no one consistently wrote a work based on the motifs of Dada Gorgud. We will talk in detail about his works "Legendary Dreams" and "Burla Khatun" in our next articles. Nabi Khazri presented the reality of the 20th century in a new spirit in his work "The Sword Stinging in the Earth" (1985). "In the work, he took a look at the epic, the poem from today's position, and mentioned the past for the sake of the future" [B.Nəbiyev, “Özümüzdən başlayaq”]. In this work, which consists of eight pictures, he added several new images - Cicek, Sildirim, Odoglu, Çapgoz, Khor, Farraşbaşı, and shortened some of the portraits and scenes. The dramatist brought the character of the minstrel to the fore here, unlike his height, he played it in every way in the work, even in the same part several times. The work begins with the praise of the fatherland of Elin Pir, the eldest son of his people. If in the epic we come across the expression "Dadam Gorgut came and robbed the family", then the playwright not only gave our great singer Deda Gorgu a large place in the play, but also managed to raise the gopuz, a symbol of the national character, to the level of a character. Gopuz is mentioned in two places in the first scene of the drama.